Polarization-Singular Approach to Imaging Mueller-Matrix Polarimetry in the Differential Diagnosis of Histological Sections of Biopsy of Tumors of the Uterus and Prostate - Dubolazov, A.; Ushenko, V.; Trifonyuk, L.; Stashkevich, A.; Soltys, I.; Ushenko, Y.; Tomka, Y.; Ushenko, A.; Gantyuk, V.; Gorodensky, P. (Frontiers in Physics, 2021)
The possibilities of the diagnostic use of the singular approach of the distributions of the number of characteristic values of the MMI is effective for differentiating the polarization properties of histological biopsy sections of benign and malignant tumours of the uterus and prostate. Within the framework of evidence-based medicine, the sensitivity, specificity and accuracy of the azimuthal-invariant express (∼15 min) method of Mueller-matrix mapping of polarization-singular states in the differential diagnosis of uterine myoma and adenocarcinoma, as well as adenocarcinoma of the prostate with varying degrees of differentiation have been determined.